Depositional provenance of the Greater Himalayan Sequence, Garhwal Himalaya, India: Implications for tectonic setting - Spencer, Christopher; Harris, R.A.; Sachan, H.; Saxena, A. (Springer, 2011)
The Greater Himalayan Sequence in the Garhwal Region of India is a 14–20 km thick succession of various pelitic and psammitic metasediments which contain individual units that are traceable for at least 250 km along the strike of the Himalayan range in northwestern India. Bulk rock geochemical analyses show a chemical index of alteration (CIA) values of 57–93 with an average of 67, average (La/Yb)N = 18.6, average (La/Sm)N = 3.7, Cr/Th range between 0.2 and 214.5, and Th/Sc range between 0.2 and 10.3. The various geochemical tectonic indicators reveal a signature akin to an active continental margin. A low degree of weathering and high concentrations of incompatible/compatible element ratios respectively point to a proximal and primarily a silicic source region. The occurrence of three-phase halite bearing primary fluid inclusions in the quartz grains of metasediments indicate their provenance from a magmatic terrain. Potential source regions of the Greater Himalayan Sequence are the East African Orogeny, the East Antarctic Orogeny, and/or the Bhimpedian Orogeny of Northern India. Fluid inclusions in the Greater Himalayan Sequence (three-phase halite bearing inclusions, moderately high temperature bi-aqueous inclusions, and carbonic-aqueous inclusions) estimate maximum salinity at ~33 wt.% NaCl. This occurrence of fluid inclusions is also consistent with a magmatic terrain.